Hydro-Social Interactions in the Arsenic Hotspot Regions of India - Ranjan, Avinash; Mandal, Kajal Kumar; Meena, Mukesh Kumar; Meena, M.L. (National Geographical Journal of India, 2022)
Water is a precious gift of nature provided to humans to sustain on the surface of the earth. Overexploitation of this fundamental resource in an unsustainable manner has deteriorated its natural state. Today, billions of people around the world do not have drinking water on their premises. A large proportion of this limited resource is contaminated and is not t for consumption.An elevated level of arsenic in the ground watersis one of the worst anthropogenically produced disasters ever. It is one of the contaminants of water resources, which is both naturally present and anthropogenically produced. It is termed as “the king of poison” due to its high toxicity. It has taken more lives than any other toxicity on the earth. More than one billion people in India are currently affected by arsenic-contaminated water and its manifested diseases, particularly in the Ganga-Brahmaputra-Meghna Plains. It has produced a wide range of difculties for the inhabitant in the affected areas, including health problems, social problems, and economic problems. There are ample studies available dealing with health burdens arising out of consuming arsenic-contaminated water. Still, there is a shortage of studies concentrating on the socioeconomic issues arising out of it. This paper reviews all the previous works on arsenic contamination and related problems. It emphasizes the socio-economic aspects of the problem and analyzes India's arsenic hotspot regions. The study points out that arsenic has put health burdens on the inhabitant and created many interrelated socio-economic issues that need to be taken into proper consideration for future research.